Non epistemic perception and subeventive structure - Carrasco Gutiérrez, Ángeles (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2017)
States and null transition processes are the two types of events that are excluded from the infinitive clauses embedded to the Spanish verb ver, ‘to see’. The reason is that none of them provide changes of properties or locations that can be perceived. This is the lexical requirement that the visual perception verb imposes to its complements. In this paper, they are examined the conditions under which certain null transition processes can appear in non-epistemic or direct perception contexts: (a) the existence of external boundaries; (b) the inexistence of presupposed states related to the asserted states; and (c) the possibility that null transition (macro)processes are analyzed in terms of non-null transition (micro)processes.